Realism and the Symbol of Cafe in Ernest Hemingway’s A Well-Lighted Place - Eva Fatimah (Metaphor, 2020)
This study aims to identify the elements of realism contained in the short story entitled A Clean Well Lighted Place by Ernest Hemingway. This study uses qualitative research method. The approach used is literary sociology using structuralism theory focusing on the analysis of intrinsic elements, namely character and setting. The analysis shows that this short story represents Ernest Hemingway's realism. This can be seen from the appearing characters and settings which are part of the middle or lower class society. In addition, the cafe in this short story also shows the author's desire for a peaceful social situation; the opposite of industrialization which is full of greed.